Effect of total splenectomy in the lipid profile in mice - Demuner,Bianca Lacerda (2015)
PURPOSE: To analyze total splenectomy effect on the lipid profile - total cholesterol, low-density lipoprotein cholesterol (LDL), high-density lipoprotein cholesterol (HDL), very-low-density lipoprotein cholesterol (VLDL) and triglycerides levels, in Balb/c mice.METHODS: Thirty Balb/c male mice, one (1) month old and average weight 26.2g ± 4.0 were used in the experiment. They were distributed into three groups of 10 animals each: a control group (non-operated), a simulation group (spleen manipulation) and the splenectomy group. The animals were subjected to blood sampling to measure plasma lipid levels, at three different times: before surgery, days 30 and 75 of the experiment.RESULTS: Increased total cholesterol and LDL were observed in the control group from the start to end of the experiment. The simulation group showed increased rates of VLDL and triglycerides at the 30th and 75th days. Splenectomized animals showed no significant change.CONCLUSION: Total splenectomy did not induce increased plasma lipids levels of in Balb/c mice.